2023
DOI: 10.1186/s12906-022-03811-x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of communication training for Chinese medicine practitioners in Hong Kong to integrate patients’ conventional medical history

Abstract: Background Despite Traditional Chinese medicine’s (TCM) historical roles in Chinese society, few research has been investigated the nature of TCM practitioner–patient interactions. Improved communication skills among TCM practitioners will result higher-quality interactions and better clinical outcomes. Methods To investigate the changes in TCM practitioners’ communication practices after communications training focused on promoting their awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Additionally, many of the respondents felt that HZ patients had a harder time understanding a TCM doctor’s remarks than a WM doctor, which may be at odds with earlier results. 51 It has been shown that TCM practitioners have better communication skills than their Western counterparts, which positively impacts their interactions with patients. 51 Effective medical communication can impact treatment adherence, satisfaction, and pain management outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many of the respondents felt that HZ patients had a harder time understanding a TCM doctor’s remarks than a WM doctor, which may be at odds with earlier results. 51 It has been shown that TCM practitioners have better communication skills than their Western counterparts, which positively impacts their interactions with patients. 51 Effective medical communication can impact treatment adherence, satisfaction, and pain management outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 51 It has been shown that TCM practitioners have better communication skills than their Western counterparts, which positively impacts their interactions with patients. 51 Effective medical communication can impact treatment adherence, satisfaction, and pain management outcomes. 52 In China, HCPs are mainly trained to communicate direct medical information rather than address patients’ emotional needs.…”
Section: Discussionmentioning
confidence: 99%